Cloning, Characterization, and Copy Number of the Murine Survival Motor Neuron Gene: Homolog of the Spinal Muscular Atrophy-Determining Gene - DiDonato, Christine J.; Chen, Xiao-Ning; Noya, David; Korenberg, Julie R.; Nadeau, Joseph H.; Simard, Louise R. (Genome Research, 1997)
Because of a 500-kb inverted duplication, there are two copies of the survival motor neuron (SMN) gene in humans, cenSMN and telSMN. Both genes produce identical ubiquitously expressed transcripts; however, only mutations in telSMN are responsible for spinal muscular atrophy (SMA), the second most common autosomal recessive childhood disease. We have cloned the murine homolog Smn and mapped the gene to Chromosome 13 within the conserved syntenic region of human chromosome 5q13. We show that the Smn transcript (1.4 kb) is expressed as early as embryonic day 7. In contrast to humans, we found no evidence of alternative splicing. The predicted amino acid sequence between mouse and human SMN is 82% identical, and a putative nuclear localization signal is conserved. FISH data indicate that the duplication of the SMA region observed in humans is not present in the mouse. We also found no evidence of multiple Smn genes using Southern blot hybridization and single-strand conformation analysis. Using these methods, we detected at least four copies of Naipexon 5 clustering distal to Smn. Finally, three biallelic markers were identified within the Smn coding region; two are silent polymorphisms, whereas the third changes a cysteine residue to a tyrosine residue in exon 7. Overall, our results indicate thatSmn is single copy within the mouse genome, which should facilitate gene disruption experiments to create an animal model of SMA.[The murine Smn cDNA sequence has been submitted to GenBank under accession no. U77714. The Mouse Genome Database accession no. for FISH mapping of Smn andNaip is MGD-INEX-31 and for the genetic mapping of theSmn exon 2b microsatellite marker is MGD-CREX-705.]
10.1101/gr.7.4.339